An Overview of Accounting Ethics Course In Undergraduate Program Curriculum In Indonesia - Limijaya, Amelia (AKRUAL: JURNAL AKUNTANSI, 2018)
This research describes the status of accounting ethics course in accounting undergraduate program curriculum in Indonesia, which is based on the data available from the National Accreditation Agency for Higher Education website. The sample consists of 60 programs which have an accreditation status of A and the status is not expired yet. The result suggests that the majority of the programs offer an accounting-specific course and only a few of them have two stand-alone course on ethics in their curriculum. Not much differences are found regarding the naming of the course. Variations are observed regarding the course placement, nature of the course and the required prerequisites. Suggestions given include covering accounting ethics topic in the curriculum, preferably in a stand-alone course, or integrating it into other courses if a stand-alone one is not feasible and making sure that the learning outcomes related to accounting ethics are actually covered.Â